Structure Formation and Curing Stage of Arbolite–Concrete Composites Based on Iron-Sulfur Binders - Baizak Isakulov; Abilkhair Issakulov; Agnieszka Dąbska (Infrastructures)
The paper deals with the issue of obtaining iron-sulfur-containing binders through their mechanochemical treatment using mutual neutralization and detoxification structure formation, and the curing stage of arbolite concrete composites based on industrial waste under long-term loading were also studied. Due to abrasion and impact, the mutual neutralization and detoxification methods of industrial waste toxic components through their mechanochemical treatment on the structures of ball mill LShM-750, were used to obtain iron-sulfur-containing binders. Pyrite cinders acted as oxidizing agents, and elementary technical sulfur had reduced properties. To determine the rate of creep strain growth, the load on prism samples was applied in the form of specially made spring units at stress levels of 0.15 Rbn, 0.44 Rbn, and 0.74 Rbn, where Rbn is the prism strength of iron-sulfur-containing arbolite concrete in compression. The strength and fracture formations of lightweight iron-sulfur concrete were studied using strain gauge apparatus and depth strain gauges glued on shredded reed fibers using adhesive, installed before concreting. It was revealed that the introduction of a sulfur additive within the range from 10 to 13% increases the compressive strength of iron-sulfur-containing concrete composites prepared with that of mortars at a water/solid ratio equal to 0.385 in wet and dry states. It is found that the deformations occurring under applied load growth proportionally to it, and deviation from this regularity was observed for lightweight iron-sulfur-containing concrete only at high compressive stresses. It was also proved that the destruction of iron-sulfur-containing arbolite occurs sequentially. First, the destruction of the mortar component is observed, and then the organic aggregate in the form of crushed reed fiber is destroyed. It was confirmed that arbolite concrete composite can be used as an effective wall material for civil engineering structure, especially in seismic regions of Kazakhstan.